Revisiting the drug crop eradication-violence nexus: a mixed-methods analysis of conflict and cooperation in traditional governance communities in Oaxaca, Mexico - Gabriel Tamariz; Brian C. Thiede; Karl S. Zimmerer (Ecology and Society, 2025)
Illegal crop cultivation is commonly assumed to be related to physical violence. However, consistent with the literature on natural resources access and control, findings on the illegal drug crop eradication-violence nexus are inconsistent. The lack of empirical consensus suggests the need for new conceptual and methodological approaches to investigate the local histories and broader power relations that illegal crop cultivation is embedded in. Using collective action theory and a conceptual integration of social-ecological systems and political ecology, we interrogate the relevance and limitations of local traditional governance and conflict management institutions in fostering cooperation and mitigating violence associated with illegal crop production within communities and vis-à-vis external actors (i.e., the military and drug trafficking organizations). We conducted a mixed-methods analysis of both official statistics on crop cultivation and violence and qualitative interviews in prisons in the state of Oaxaca, Mexico. We first found a statistically significant, non-linear association between illegal crops and homicides, with cultivation generally increasing homicides but the effect moderating at high levels of cultivation. Secondly, our qualitative analyses suggest that the limited magnitude of these estimated effects is partly due to the predominance of existing collective action institutions that were mobilized and prevented the transformation of the agrarian system. Third, we show how these institutions do not guarantee intra- and supra-community cooperation. Effective conflict management additionally requires illegal crop cultivation to be economically relevant and morally sanctioned among community members. By analyzing both general trends and in-depth (counter)examples, the paper questions the essentialized depictions of peasant illegal-crop growers and their violent and non-violent resistance to change and oppression.